Tribological properties of a diamond-like carbon film under lubrication with commercial fully formulated oils - Hikaru OKUBO; Hirochika FUKUDA; Ryo TSUBOI; Chiharu TADOKORO; Shinya SASAKI (Nihon Kikai Gakkai ronbunshu, 2016)
Tribological properties of a diamond-like carbon film were investigated under lubrication with commercial fully formulated oils. Friction tests were carried out for a hydrogenated amorphous carbon (a-C:H)/steel tribopair under lubrication with the four types of fully formulated oil using a reciprocating type ball-on-disk tribo-tester. To clarify the friction and wear mechanisms, surface analysis, such as Raman spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray analysis (EDS) and atomic force microscopy (AFM), were conducted on the wear tracks of a-C:H disks. The results of friction tests and surface analysis show that the properties of tribofilms on DLC films play important roles in determining the tribological properties of DLC films under lubrication with fully formulated oils.